SYSTEM OF HIGHER EDUCATION IN SWITZERLAND - M. S. Dushenok (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2016)
The article describes the system of higher education in Switzerland which is funded by private sector. Swiss higher education follows the three-tiered structure of Bachelor's, Master's and doctoral studies (with PhD titles being reserved to federal institutes of technology and cantonal universities). All the universities are divided into federal institutes of technology (namely Swiss Federal Institute of Technology and Ecole Polytechnique Fédérale de Lausanne), cantonal universities (there are ten of them), universities of teacher education (comprising fourteen UTEs and four other teacher training institutions such as the Swiss Federal Institute for Vocational Education and Training and the Swiss Federal Institute of Sports Magglingen) and universities of applied sciences (providing 300 degree programmes). In Switzerland traditional institutions are centered on basic research, while others are based on applied research. Courses at the graduate level are taught in English. Structure of the studies depends on faculty involved. For instance, almost all disciplines require 8-9 semesters to graduate. The system of higher education in Switzerland is deeply integrated into European one. It provides universities with range of opportunities to collaborate with other outstanding universities all over the world. Also the benefits of such system of higher education are described.